Engineering Cell‐Free Protein Synthesis for High‐Yield Production and Human Serum Activity Assessment of Asparaginase: Toward On‐Demand Treatment of Acute Lymphoblastic Leukemia. Issue 4 (20th January 2020) - Hunt, J. Porter; Wilding, Kristen M.; Barnett, R. Jordan; Robinson, Hannah; Soltani, Mehran; Cho, Jae Eun; Bundy, Bradley C.
Abstract: Acute lymphocytic leukemia (ALL) is a common childhood cancer in the United States, with over 6000 new cases diagnosed each year. Administration of bacterial asparaginase (ASNase) has improved survival rates to nearly 80%, however these therapeutics have high incidence of immunological neutralization and serum activity must be monitored for most effective treatment regimens. Here, a 72% improvement in cell‐free protein synthesis (CFPS) of FDA approved l ‐asparaginase (crisantaspase) is demonstrated by employing an aspartate‐fed‐batch reactor format. A CFPS‐based ASNase activity assay as a tool for therapeutic regimentation and production quality control is also presented. This work suggests that shelf‐stable and low‐cost Escherichia coli ‐based CFPS reactions may be employed on‐demand to 1) synthesize biologics on‐site for patient administration, 2) verify biologic activity for dosage calculations, and 3) monitor therapeutic activity in human serum during the treatment regimen. The combination of both therapeutic production and activity assessment introduces a concept of synergistic utility for bacterial cell lysates in modern medical treatment. Indeed, recent work with CFPS biosensors supports a not‐too‐distant future when shelf‐stable E. coli CFPS systems are used to diagnose, treat, and monitor treatment of diseases in the clinical setting. Abstract : Bacterial l ‐asparaginases are critical therapeutics which have helped increase acute lymphoblastic leukemia survival rates. Employing an inhibitor of l ‐asparaginase (ASNase) in Escherichia coli cell‐free protein synthesis (CFPS) reactions increased ASNase production yields by 70%. Furthermore, a rapid E. coli CFPS ASNase activity assay was developed and validated in 44% human serum as a potential quality control and treatment effectiveness tool.